Science of the anesthetic efficacy of articaine and lidocaine in lower third molar extractions. A literature review - Espinoza Plaza, Jose (2022)
The efficacy of a local anesthetic in a surgical procedure such as lower third molar extraction is very important given the complexity of this procedure such as incision, flap, odontosection and ostectomy, curettage, lavage and suture. Local anesthetics are drugs that reversibly inhibit nerve conduction in the area where they are applied (Almeida et al., 2020), inhibiting the perception of pain, with the sequence being: increased skin temperature and vasodilation, loss of pain and thermal sensitivity, loss of perception, loss of sensation of touch and pressure and loss of motor skills(Arribas Blanco et al., 2001), the anesthetic effect varies between 2 to 4 hours approximately. Currently, several studies suggest that Articaine 4% should be used in extractions of lower third molars because it has better clinical properties compared to Lidocaine 2%, both associated with epinephrine 1: 100,000000  (Almeida et al., 2020) (Zhang et al., 2021) (Vademecun, 2020) (Larocca de Geus et al., 2020) (Rossi et al., 2021) (Baeza et al., 2020),  , these are amide group anesthetics and both have been shown to be safe for any dental procedure that requires avoiding intense pain (endodontics, restorations, extractions, etc.).